Lungs from donors ≥70 years of age for transplantation - do long-term outcomes justify their use? - Sommer, Wiebke; Franz, Maximilian; Aburahma, Khalil; Saipbaev, Akylbek; Flöthmann, Katharina; Yablonski, Pavel; Avsar, Murat; Tudorache, Igor; Greer, Mark; Haverich, Axel; Welte, Tobias; Kuehn, Christian; et al. (Transplant international, 2023)
Donor shortages have led transplant centers to extending criteria for lung donors. Accepting lung donors ≥70 years of age have previously shown good short-term outcomes, however no mid- and long-term outcome data on these extended criteria donors has been published to date. An analysis including all patients undergoing lung transplantation between 06/2010 and 12/2019 were included into the analysis, comparing outcomes between patients receiving organs from donors <70 years of age to patients being transplanted with donors ≥70 years old. Among the 1168 lung-transplanted patients, 62 patients received lungs from donors ≥70 years old. Recipient age of those receiving older organs was significantly higher and candidates were more likely to suffer from obstructive lung disease. Older donors were exposed to significantly shorter periods of mechanical ventilation prior to donation, had higher Horowitz indices and were less likely to have smoked. Postoperative time on mechanical ventilation, time on ICU as well as total hospital stay were comparable. Overall survival as well as CLAD-free survival showed no differences between both groups in the follow-up period. Utilization of donor lungs ≥70 years leads to excellent mid- and long-term results that are similar to younger donor organs when carefully preselecting these older organs.